2014
DOI: 10.1093/ilar/ilt045
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Animal Care and Use Committee Considerations for Animal Models of Peripheral Neuropathy

Abstract: Peripheral neuropathy and neuropathic pain are debilitating, life-altering conditions that affect a significant proportion of the human population. Animal models, used to study basic disease mechanisms and treatment modalities, are diverse and provide many challenges for institutional animal care and use committee (IACUC) review and postapproval monitoring. Items to consider include regulatory and ethical imperatives in animal models that may be designed to study pain, the basic mechanism of neurodegeneration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…All rats had recovered from anesthesia within 5 minutes and were walking normally without altered gait. Following recovery from anesthesia the subjects did not demonstrate observable pain behaviors 51 nor clinical evidence of tissue injury. Throughout the duration of the study all the rats were observed to have normal gait and were without visible evidence of inflammation, swelling, increased warmth, weakness, deformities or positional changes noted on the operated hindpaw, at any time.…”
Section: Resultsmentioning
confidence: 93%
“…All rats had recovered from anesthesia within 5 minutes and were walking normally without altered gait. Following recovery from anesthesia the subjects did not demonstrate observable pain behaviors 51 nor clinical evidence of tissue injury. Throughout the duration of the study all the rats were observed to have normal gait and were without visible evidence of inflammation, swelling, increased warmth, weakness, deformities or positional changes noted on the operated hindpaw, at any time.…”
Section: Resultsmentioning
confidence: 93%
“…All rats had recovered from anesthesia within 5 minutes and were walking normally without altered gait. Following recovery from anesthesia the subjects did not demonstrate observable pain behaviors (65) or clinical evidence of tissue injury. Throughout the duration of the study all the rats were observed to have normal gait and were without visible evidence of inflammation, swelling, weakness, deformities or positional changes noted on the operated hindfoot, at any time.…”
Section: Behavioral Observationsmentioning
confidence: 93%